ANALISIS JARINGAN KOMUNIKASI INFORMAL “ADIDAS TEAM” DI PT. DAMCO INDONESIA JAKARTA PUSAT - FITRIANI FITRIANI (Universitas Mercu Buana, 2016)
Informal communication has grown in line with formal communication. Informal communication is communication between people in an organization, but not planned or not specified in the organizational structure. Problems penelitin how the role and model of informal communication network in PT. Damco Indonesia Jakarta.. This research type is descriptive research with quantitative approach with method of communication network analysis. Primary data were collected from the questionnaire and the data obtained will be analyzed by sociometric technique. The results of this study found the existence of individual roles in communication networks consisting of Opinion Leader, Liason, Neglectee, Cosmopolite, Gate Keeper. In this informal communication network there are also 5 clicks with 4 clicks that make up the circle model and one click that make up the Wheel model. Roles found: Opinion Leader 4 people, Liason 2 people, Bridge as many as 5 people, Cosmopolite 2 people, Gate keeper 1 person, Neglectee 2 people and 1 Star.Komunikasi informal turut berkembang sejalan dengan komunikasi formal. komunikasi informal adalah komunikasi antara orang yang ada dalam suatu organisasi, akan tetapi tidak direncanakan atau tidak ditentukan dalam struktur organisasi. Permasalahan penelitin bagaimana peran dan model jaringan komunikasi informal di PT. Damco Indonesia Jakarta. Tipe penelitian ini adalah penelitian deskriptif dengan pendekatan kuantitatif dengan metode analisis jaringan komunikasi. Data primer dikumpulkan dari kuesioner dan data yang diperoleh akan dianalisis dengan teknik sosiometri. Hasil penelitian ini menemukan adanya peran-peran individu dalam jaringan komunikasi yang terdiri dari Opinion Leader, Liason, Neglectee, Cosmopolite, Gate Keeper. Pada jaringan komunikasi informal ini juga terdapat 5 klik dengan 4 klik yang membentuk model circle dan satu klik yang membentuk model Wheel. Peran- peran yang ditemukan : Opinion Leader 4 orang, Liason 2 orang, Bridge sebanyak 5 orang, Cosmopolite sebanyak 2 orang, Gate keeper 1 orang, Neglectee 2 orang dan 1 orang Star.